2011
DOI: 10.1007/s00436-011-2695-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of the essential oil of Piper cubeba L. (Piperaceae) against Schistosoma mansoni

Abstract: In this paper, cercariae, schistosomula, and adult Schistosoma mansoni worms were incubated in vitro with the essential oil of Piper cubeba (PC-EO) at concentrations from 12.5 to 200 μg/mL, and the viability was evaluated using an inverted microscopy. The effects of PC-EO at 100 and 200 μg/mL on the stages of S. mansoni were similar to those of the positive control (PZQ at 12.5 μg/mL), with total absence of mobility after 120 h. However, at concentrations from 12.5 to 50 μg/mL, PC-EO caused a reduction in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 33 publications
5
35
1
1
Order By: Relevance
“…Acetate carvacrol (6.25 µg/mL) affected motility, parasite tegument and oviposition [7]. Similar results were also found for phloroglucinol derivatives (aspidina, flavaspidico acid, methylenebis-aspidinol and desaspidina) [21], dermaseptina antimicrobial peptide [27], essential oils of Piper cubeba and Tagete serecta [21,28], (+)-Epoxy-Limonene [29] and Mitracarpus frigidus methanolic extract [30].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Acetate carvacrol (6.25 µg/mL) affected motility, parasite tegument and oviposition [7]. Similar results were also found for phloroglucinol derivatives (aspidina, flavaspidico acid, methylenebis-aspidinol and desaspidina) [21], dermaseptina antimicrobial peptide [27], essential oils of Piper cubeba and Tagete serecta [21,28], (+)-Epoxy-Limonene [29] and Mitracarpus frigidus methanolic extract [30].…”
Section: Discussionsupporting
confidence: 52%
“…PZQ (5 μM) also caused 100% mortality with tegumental alterations, whereas no effect was observed in worms in the negative (RPMI 1640 medium) and control (RPMI medium plus 0.5% DMSO) groups. Natural products are promising sources of new potentially therapeutic compounds, and several lignans, especially dibenzylbutyrolactones, have been reported as promising sources of antiparasitic compounds against neglected parasitic diseases [21]. In this sense, arctiin has also been assessed against some parasites ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…6). In contrast, in a study of S. mansoni schistosomula incubated with essential oil from the fruit of the Piper cubeba plant, the authors reported some morphological changes and granularity of the parasite [30]. Unlike adult worms, which showed tegumental damage (Fig.…”
Section: Effect Of Epiisopiloturine On S Mansoni Schistosomula Of DImentioning
confidence: 82%
“…In addition, the literature suggests that the essential oil obtained from some species of Piper also have various biological activities, such as anti-parasitic, insecticidal, larvicidal, antimicrobial, antifungal and antioxidant properties Misni et al, 2011;Salleh et al, 2011;da Silva et al, 2010da Silva et al, , 2011Monzote et al, 2010;Magalhães et al, 2012).…”
Section: Discussionmentioning
confidence: 98%